Threshold concepts, conceptions and skills: Teachers' experiences with students' engagement in functions. - Kallia, Maria; Sentance, Sue (Journal of Computer Assisted Learning, 2021)
Threshold concepts have been characterised in the literature as jewels in the curriculum as they can inform teaching and learning practices. Therefore, identifying and addressing threshold concepts in any discipline is critical. The aim of the current study is to explore the existence of threshold concepts in computer programming and specifically with regard to the area of functions. Based on our previous works in which we identified 11 potential threshold concepts in functions by employing the Delphi method and seven misconceptions that students hold in this area of programming, the current study further explores computing teachers' experiences with students' engagement with 4 of the 11 concepts using an interpretative phenomenological analysis of interviews. The analysis revealed that from these concepts, we could argue that parameters, parameter passing and return values likely form a threshold conception and procedural decomposition is a procedural threshold (threshold skill). The study presents our framework that lead us to the identification of these thresholds in computer programming, presents the computing teachers experiences with these concepts and concludes with the implication of these results on students' learning and teaching practices in computer programming. Lay Description: What is already known about this topic: Threshold concepts are concepts that are particularly troublesome for students basically because of their transformative and integrative characteristics.Students struggle to understand these concepts and therefore learning becomes a barrier.In computer programming, research suggests that concepts like object‐oriented programming, recursion, pointers are examples of threshold concepts, but more research is needed to identify more threshold concepts and how students experience these concepts. What this paper adds: The paper explores teachers' experiences teaching the concepts: parameters, parameter passing, return values and procedural decomposition and identifies common students' learning difficulties with these concepts.The paper investigates students' transformations and integration of knowledge once they have understood these concepts through the teachers' reflective practice.The paper suggests that parameters, parameter passing and return values form a threshold conception in programming and that procedural decomposition is a procedural threshold. Implications for practice and/or policy: The paper highlights many problematic and troublesome areas in functions in which students experience many difficulties. This specific output can be used by teachers who would like to organise their lessons around difficult points in functions and prepare appropriate materials that will help students overcome the corresponding obstacles.The paper identifies epistemological and ontological transformations that students experience once they overcome the conceptual difficulties and finally grasp the threshold concepts. This outcome has a significant impact on the teaching of computer programming. Teachers should take into consideration the powerful conceptual relationships these concepts form and the transformations that students' exhibit by creating learning environments that will bring about these transformations and assist students in their attempt to understand and identify themselves in the computer classroom.